Primary school teachers perception of technological pedagogical content knowledge in online learning due to Covid 19 - Junita Cristi Makawawa; Ali Mustadi; Jewish Van Septriwanto; Falenthino Sampouw; Roeth A.O Najoan (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
Primary school teachers need to have technological knowledge, pedagogical knowledge, and content knowledge in online teaching. TPACK is an integrative and transformative knowledge that teachers need to use technology effectively and efficiently in the classroom. This article investigates primary school teachers' perceptions of Technological Pedagogical Content Knowledge (TPACK) competencies in implementing online learning due to the pandemic COVID-19. The sample in this study were 117 primary school teachers in North Sulawesi province. The method used is a quantitative descriptive approach. Data was collected using a questionnaire on a Likert scale developed in Google Form. The results showed that most primary school teachers in North Sulawesi, Indonesia, already had TPACK competencies in online learning during the COVID-19 pandemic. Even so, TPACK competencies are in need to be improved in the abilities of TK and PK. The correlation results between the TPACK constructs also showed that the PK and TPK components had a significant effect on TPACK primary school teachers' perception of online learning. It was also found that there was no significant difference between gender and TPACK competency of primary school teachers.